CFD simulation of bubbly flow around an obstacle in a vertical pipe with a focus on breakup and coalescence modelling. (February 2021) - Tas-Koehler, Sibel; Neumann-Kipping, Martin; Liao, Yixiang; Krepper, Eckhard; Hampel, Uwe
Highlights: A breakup/coalescence model is validated for 3D flow conditions. The validation is shown for two different liquid velocities. Two-phase flow hydrodynamics under complex flow conditions is analyzed. The effects of different physical mechanisms underlying bubble breakup and coalescence are demonstrated. Abstract: In the present study, we assessed the capabilities of Eulerian-Eulerian CFD two-phase flow simulation with the homogeneous Multiple Size Group Model (MUSIG) and consideration of breakup and coalescence under three-dimensional flow conditions. We compared void fraction, bubble size and bubble velocity distributions against experimental data from vertical gas-disperse two-phase flow in a pipe with a flow obstruction. The simulation results generally agree well upstream the obstacle, where we have a typically developed pipe flow. Downstream of the obstacle void fraction is overpredicted while bubble velocity is underpredicted. The bubble size distribution has no clear trend. With higher liquid velocities, the deviations increase. As a conclusion, the simulation has difficulties to balance the gas fraction in the strong vortex in the shadow of the obstacle. Here further model improvement is needed.